Perubahan Elektrokardiografi Post-Intervensi pada Pasien dengan Atrial Septal Defect Secundum: sebuah Studi Observasional - Patimang, Yulius; Bastario, Andi Renata; Alkatiri, Abdul Hakim; Armyn, Andi Alief Utama; Idris, Irfan; Amir, Muzakkir; Nguyen, Dat T.; Qanitha, Andriany (The Indonesian Heart Association, 2025)
Background:. Secundum Atrial Septal Defect (ASD) is one of the most common forms of left-to-right shunt congenital heart defect that leads to right-sided overflow inducing geometrical and electrical changes in the right chambers. Electrocardiograms (ECGs) are reliable non-invasive tools to detect various electrical patterns produced by Secundum ASD that can give important clues in diagnostic procedures. After shunt closure, either percutaneously or surgically, normalization of flow ratio will induce reverse remodelling, which is one of the most important prognostic factors after defect closure. Our study aims to detect reverse remodelling in electrical aspects using ECGs in short (< 24 hour) and long term (> 6 months) follow-up after defect closure. Methods: We screened Secundum ASD patients that were admitted to undergo interventional closure percutaneously and surgically at RSUP Dr. Wahidin Sudirohusodo. After the screening process, 54 eligible subjects were enrolled in this study. Baseline characteristic data were obtained from medical record. ECGs measurements were taken at the time of admission for pre-closure baseline data, within 24 hours of closure and beyond 6 months after closure for follow-up data. Each ECGs parameter statistically was compared for pre-closure versus < 24 hour measurement after closure, and < 24 hour versus 6 months measurement after closure using paired T test or Wilcoxon signed-rank test. Results: In analysis of pre-closure vs. < 24 hour after closure data. There was significant reduction in all of the ECGs parameters (P wave amplitude 0.19 ± 0.04 vs. 0.11 ± 0.03 mv (p<0.001), P wave duration 97.78 ± 11.94 vs. 75.35 ± 13.36 ms (p<0.001), PR interval 182.89 ± 26.47 vs. 156.83 ± 21.81 ms (p<0.001), QRS duration 112.97 ± 14.84 vs. 88.31 ± 14.43 ms (p<0.001), QRS axis 107.94 ± 23.00 vs. 95.25 ± 24.62 ˚ (p<0.001), QTc interval 403.84 ± 30.85 vs. 396.80 ± 33.76 ms (p 0.017), R wave V1 amplitude 0.74 ± 0.35 vs. 0.53 ± 0.24 mv (p<0.001). In analysis of < 24 hour vs. > 6 months after closure data. There was also significant reduction in most of the ECGs parameters (P wave duration 75.05 ± 13.82 vs. 69.46 ± 11.84 ms (p<0.001), PR interval 155.53 ± 22.82 vs. 148.30 ± 19.34 ms (p<0.001), QRS duration 89.74 ± 14.02 vs. 85.38 ± 14.22 ms (p<0.001), QRS axis 94.80 ± 23.57 vs. 81.26 ± 22.96 ˚ (p<0.001), QTc interval 396.22 ± 33.70 vs. 384.40 ± 37.87 ms (p 0.020), R wave V1 amplitude 0.51 ± 0.24 vs. 0.32 ± 0.21 mv (p<0.001), except P wave amplitude (0.121 ± 0.03 vs. 0.119 ± 0.03 ms (p 0.321)). Conclusion: Our study showed electrical reverse remodelling in the most of the ECGs parameters after Secundum ASD closure except P wave amplitude in long term follow up.